Polarographic Study of Stability Constants of Cadmium(II) Complexes with β-picoline and Some Hydroxy Acids - Chauhan, P.K.S.; Verma, Amit; Paliwal, R.K (Asian Journal of Chemistry, 2016)
The mixed ligand complexes of b-picoline (b-pico), malate (mal2–) and tartrate (tart2–) with Cd(II) have been studied polarographically at constant ionic strength (μ = 1.5 M, NaNO3) and pH 5.95 at 25 ± 0.1°C. The reduction of the complexes at d.m.e. is reversible and diffusion-controlled. Three mixed complexes [Cd(mal)(b-pico)], [Cd(mal)(b-pico)2] and [Cd(mal)2(b-pico)]2– are formed in Cd(II) b-picoline-malate system with the stability constants log b11 = 2.7224, b12 = 4.2805 and b21 = 3.9661. Two mixed complexes [Cd(b-pico)(tart)] and [Cd(b-pico)2(tart)] are formed in Cd-b-picolinetartrate system are their stability constants are found to be log b11 = 2.1368 and log b12 = 4.1065, respectively.